Activin Controls Ethanol Potentiation of Inhibitory Synaptic Transmission Through GABAA Receptors and Concomitant Behavioral Sedation - Zheng, Fang; Puppel, Anne; Hubert, Sabine E.; Link, Andrea; Eulenburg, Volker; van Brederode, Johannes; Müller, Christiane; Alzheimer, Christian (Neuropsychopharmacology, 2016)
Activin, a member of the transforming growth factor-? family, exerts multiple functions in the nervous system. Originally identified as a neurotrophic and -protective agent, increasing evidence implicates activin also in the regulation of glutamatergic and GABAergic neurotransmission in brain regions associated with cognitive and affective functions. To explore how activin impacts on ethanol potentiation of GABA synapses and related behavioral paradigms, we used an established transgenic model of disrupted activin receptor signaling, in which mice express a dominant-negative activin receptor IB mutant (dnActRIB) under the control of the CaMKII? promoter. Comparison of GABAA receptor currents in hippocampal neurons from dnActRIB mice and wild-type mice showed that all concentrations of ethanol tested (30-150 mM) produced much stronger potentiation of phasic inhibition in the mutant preparation. In dentate granule cells of dnActRIB mice, tonic GABA inhibition was more pronounced than in wild-type neurons, but remained insensitive to low ethanol (30 mM) in both preparations. The heightened ethanol sensitivity of phasic inhibition in mutant hippocampi resulted from both pre- and postsynaptic mechanisms, the latter probably involving PKC?. At the behavioral level, ethanol produced significantly stronger sedation in dnActRIB mice than in wild-type mice, but did not affect consumption of ethanol or escalation after withdrawal. We link the abnormal narcotic response of dnActRIB mice to ethanol to the excessive potentiation of inhibitory neurotransmission. Our study suggests that activin counteracts oversedation from ethanol by curtailing its augmenting effect at GABA synapses.
EVALuna2:4739

Activin Signaling in the Pathogenesis and Therapy of Neuropsychiatric Diseases - Link, Andrea; Zheng, Fang; Alzheimer, Christian (Frontiers in Molecular Neuroscience, 2016)
Activins are members of the transforming growth factor β (TGFβ) family and serve as multifunctional regulatory proteins in many tissues and organs. In the brain, activin A, which is formed by two disulfide-linked βA subunits, is recognized as the predominant player in activin signaling. Over the last years, considerable progress has been made in elucidating novel and unexpected functions of activin in the normal and diseased brain and in deciphering the underlying molecular mechanisms. Initially identified as a neurotrophic and protective factor during development and in several forms of acute injury, the scope of effects of activin A in the adult central nervous system (CNS) has been considerably broadened by now. Here, we will highlight recent findings that bear significance for a better understanding of the pathogenesis of various neuropsychiatric diseases and might hold promise for novel therapeutic strategies. While the basal level of activin A in the adult brain is low, significant short-term up-regulation occurs in response to increased neuronal activity. In fact, brief exposure to an enriched environment (EE) is already sufficient to considerably strengthen activin signaling. Enhancement of this pathway tunes the performance of glutamatergic and GABAergic synapses in a fashion that impacts on cognitive functions and affective behavior, counteracts death-inducing signals through extrasynaptic NMDA receptors (NMDARs), and stimulates adult neurogenesis in the hippocampus. We will discuss how impaired activin signaling is involved in anxiety disorders, depression, drug dependence, and neurodegenerative diseases such as Alzheimer's and Parkinson's, and how reinforcement of activin signaling might be exploited for therapeutic interventions.
EVALuna2:32811

Deletion of interleukin-6 signal transducer gp130 in small sensory neurons attenuates mechanonociception and down-regulates TRPA1 expression - Malsch, Philipp; Andratsch, Manfred; Vogl, Christian; Link, Andrea; Alzheimer, Christian; Brierley, Stuart M.; Hughes, Patrick A.; Kress, Michaela (The Journal of Neuroscience, 2014)
Glycoprotein 130 (gp130) is the signal transducing receptor subunit for cytokines of the interleukin-6 (IL-6) family, and it is expressed in a multitude of cell types of the immune and nervous system. IL-6-like cytokines are not only key regulators of innate immunity and inflammation but are also essential factors for the differentiation and development of the somatosensory system. Mice with a null mutation of gp130 in primary nociceptive afferents (SNS-gp130(-/-)) are largely protected from hypersensitivity to mechanical stimuli in mouse models of pathological pain. Therefore, we set out to investigate how neuronal gp130 regulates mechanonociception. SNS-gp130(-/-) mice revealed reduced mechanosensitivity to high mechanical forces in the von Frey assay in vivo, and this was associated with a reduced sensitivity of nociceptive primary afferents in vitro. Together with these findings, transient receptor potential ankyrin 1 (TRPA1) mRNA expression was significantly reduced in DRG from SNS-gp130(-/-) mice. This was also reflected by a reduced number of neurons responding with calcium transients to TRPA1 agonists in primary DRG cultures. Downregulation of Trpa1 expression was predominantly discovered in nonpeptidergic neurons, with the deficit becoming evident during stages of early postnatal development. Regulation of Trpa1 mRNA expression levels downstream of gp130 involved the classical Janus kinase family-signal transducer and activator of transcription pathway. Our results closely link proinflammatory cytokines to the expression of TRPA1, both of which have been shown to contribute to hypersensitive pain states. We suggest that gp130 has an essential role in mechanonociception and in the regulation of TRPA1 expression.
EVALuna2:2455

Kdm6b and Pmepa1 as Targets of Bioelectrically and Behaviorally Induced Activin A Signaling - Link, Andrea; Kurinna, Svitlana; Havlicek, Steven; Lehnert, Sandra; Reichel, Martin; Kornhuber, Johannes; Winner, Beate; Huth, Tobias; Zheng, Fang; Werner, Sabine; Alzheimer, Christian (Molecular Neurobiology, 2016)
The transforming growth factor-? (TGF-?) family member activin A exerts multiple neurotrophic and protective effects in the brain. Activin also modulates cognitive functions and affective behavior and is a presumed target of antidepressant therapy. Despite its important role in the injured and intact brain, the mechanisms underlying activin effects in the CNS are still largely unknown. Our goal was to identify the first target genes of activin signaling in the hippocampus in vivo. Electroconvulsive seizures, a rodent model of electroconvulsive therapy in humans, were applied to C57BL/6J mice to elicit a strong increase in activin A signaling. Chromatin immunoprecipitation experiments with hippocampal lysates subsequently revealed that binding of SMAD2/3, the intracellular effectors of activin signaling, was significantly enriched at the Pmepa1 gene, which encodes a negative feedback regulator of TGF-? signaling in cancer cells, and at the Kdm6b gene, which encodes an epigenetic regulator promoting transcriptional plasticity. Underlining the significance of these findings, activin treatment also induced PMEPA1 and KDM6B expression in human forebrain neurons generated from embryonic stem cells suggesting interspecies conservation of activin effects in mammalian neurons. Importantly, physiological stimuli such as provided by environmental enrichment proved already sufficient to engender a rapid and significant induction of activin signaling concomitant with an upregulation of Pmepa1 and Kdm6b expression. Taken together, our study identified the first target genes of activin signaling in the brain. With the induction of Kdm6b expression, activin is likely to gain impact on a presumed epigenetic regulator of activity-dependent neuronal plasticity.
EVALuna2:2488

Pattern of Functional TTX-Resistant Sodium Channels Reveals a Developmental Stage of Human iPSC- and ESC-Derived Nociceptors - Eberhardt, Esther; Havlicek, Steven; Schmidt, Diana; Link, Andrea; Neacsu, Cristian; Kohl, Zacharias; Hampl, Martin; Kist, Andreas; Klinger, Alexandra; Nau, Carla; Schüttler, Jürgen; Alzheimer, Christian; et al. (Stem Cell Reports, 2015)
Human pluripotent stem cells (hPSCs) offer the opportunity to generate neuronal cells, including nociceptors. Using a chemical-based approach, we generated nociceptive sensory neurons from HUES6 embryonic stem cells and retrovirally reprogrammed induced hPSCs derived from fibroblasts. The nociceptive neurons expressed respective markers and showed tetrodotoxin-sensitive (TTXs) and -resistant (TTXr) voltage-gated sodium currents in patch-clamp experiments. In contrast to their counterparts from rodent dorsal root ganglia, TTXr currents of hPSC-derived nociceptors unexpectedly displayed a significantly more hyperpolarized voltage dependence of activation and fast inactivation. This apparent discrepancy is most likely due to a substantial expression of the developmentally important sodium channel NAV1.5. In view of the obstacles to recapitulate neuropathic pain in animal models, our data advance hPSC-derived nociceptors as a better model to study developmental and pathogenetic processes in human nociceptive neurons and to develop more specific small molecules to attenuate pain.
EVALuna2:2465

Transient receptor potential cation channel, subfamily C, member 5 (TRPC5) is a cold-transducer in the peripheral nervous system - Zimmermann, Katharina; Lennerz, Jochen K.; Hein, Alexander; Link, Andrea; Kaczmarek, J. Stefan; Delling, Markus; Uysal, Serdar; Pfeifer, John D.; Riccio, Antonio; Clapham, David E. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Detection and adaptation to cold temperature is crucial to survival. Cold sensing in the innocuous range of cold (>10-15 °C) in the mammalian peripheral nervous system is thought to rely primarily on transient receptor potential (TRP) ion channels, most notably the menthol receptor, TRPM8. Here we report that TRP cation channel, subfamily C member 5 (TRPC5), but not TRPC1/TRPC5 heteromeric channels, are highly cold sensitive in the temperature range 37-25 °C. We found that TRPC5 is present in mouse and human sensory neurons of dorsal root ganglia, a substantial number of peripheral nerves including intraepithelial endings, and in the dorsal lamina of the spinal cord that receives sensory input from the skin, consistent with a potential TRPC5 function as an innocuous cold transducer in nociceptive and thermosensory nerve endings. Although deletion of TRPC5 in 129S1/SvImJ mice resulted in no temperature-sensitive behavioral changes, TRPM8 and/or other menthol-sensitive channels appear to underpin a much larger component of noxious cold sensing after TRPC5 deletion and a shift in mechanosensitive C-fiber subtypes. These findings demonstrate that highly cold-sensitive TRPC5 channels are a molecular component for detection and regional adaptation to cold temperatures in the peripheral nervous system that is distinct from noxious cold sensing.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Nociception; Pain; Single-fiber; Temperature sensing; Thermo-transient receptor potential